How to never look fat again : over 1000 ways to dress thinner-without dieting! - Krupp, Charla (Springboard Press, 2010)
Krupp shares smart, easy ways to hide arm flaps, big busts, muffin tops, back fat, Buddha belly, booty, wide hips, thunder thighs, and heavy calves. She also looks at special problems like how not to look fat in workout gear, evening wear, and even in a swimsuit!